1985
DOI: 10.1002/pros.2990070209
|View full text |Cite
|
Sign up to set email alerts
|

Changes in immunohistochemical staining in prostatic adenocarcinoma following diethylstilbestrol therapy

Abstract: Twenty-eight pretreatment and posttreatment biopsies from 11 cases of prostatic adenocarcinoma were stained for prostate-specific acid phosphatase (PAP), prostate-specific antigen (PSA), and keratin to determine the effect of hormonal (diethylstilbestrol) therapy on these immunological markers. Treatment intervals ranged from 2 to 63 months. All pretreatment tumors were strongly positive for PAP, and nine were strongly positive for PSA. Two were weakly positive for PSA, and all were negative for keratin. In fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…It might be speculated that, as prostate tumors become less differentiated, the gene coding for PSP is somehow suppressed. A decreased expression of other prostate tumor markers, such as PAP and PSA, has been observed as the tumor becomes less differentiated (Epstein and Eggleston, 1984), as has reduced tumor marker expression following hormone treatment (Grignon and Troster, 1985). Abrahamsson et al (1988) reported that PAP, PSA and PSP all showed greater staining variability in the moderately and poorly-differentiated tumors when compared to well-differentiated tumors, and that almost identical distribution of PSA and PSP was found in the moderately to poorly-differentiated prostate carcinomas.…”
Section: Lrnrnunoperoxidase Stainingmentioning
confidence: 96%
“…It might be speculated that, as prostate tumors become less differentiated, the gene coding for PSP is somehow suppressed. A decreased expression of other prostate tumor markers, such as PAP and PSA, has been observed as the tumor becomes less differentiated (Epstein and Eggleston, 1984), as has reduced tumor marker expression following hormone treatment (Grignon and Troster, 1985). Abrahamsson et al (1988) reported that PAP, PSA and PSP all showed greater staining variability in the moderately and poorly-differentiated tumors when compared to well-differentiated tumors, and that almost identical distribution of PSA and PSP was found in the moderately to poorly-differentiated prostate carcinomas.…”
Section: Lrnrnunoperoxidase Stainingmentioning
confidence: 96%
“…The early studies on the effects of androgen deprivation on prostate tissue led to the ground‐breaking discovery of Huggins and Hodges 19,20 of the androgen‐dependent nature of prostate cancer. Oestrogen treatment leads to prominent squamous metaplasia of benign prostate glands and a reduction in the number and size of prostatic adenocarcinoma cells 21,22 . Prominent nuclear pyknosis is seen, and cytoplasmic vacuolation with ballooning and signet ring cells is commonly noted.…”
Section: Hormone Therapymentioning
confidence: 99%
“…Oestrogen treatment leads to prominent squamous metaplasia of benign prostate glands and a reduction in the number and size of prostatic adenocarcinoma cells. 21,22 Prominent nuclear pyknosis is seen, and cytoplasmic vacuolation with ballooning and signet ring cells is commonly noted. Cell rupture may be identified, and the stroma is often pale-staining and may be vacuolated or fibrotic.…”
Section: Hormone Therapymentioning
confidence: 99%
“…The top three genes, KLK3 (PSA), MSMB (beta-microseminoprotein), and TMEPAI (transmembrane prostate androgen-induced protein) were all previously well known to be regulated by androgens in human prostate [31], [32], [33]. Several other genes identified as up-regulated in human TZ xenografts by testosterone have also been previously shown to be regulated by androgens.…”
Section: Resultsmentioning
confidence: 96%